SOCIAL PEDAGOGICAL PROBLEMS OF TEACHING RUSSIAN TO STUDENTS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article examines the social-pedagogical challenges in teaching Russian to students, focusing on the linguistic, cultural, and methodological difficulties that impact learning outcomes. The study explores how socio-economic factors, differing educational backgrounds, and linguistic diversity influence students' ability to master Russian. Through literature review, analysis of teaching methods, and examination of empirical data, the article aims to provide educators with insights and recommendations to enhance the teaching process for diverse student populations.